The optimum of wave forces acting on axisymmetric, paraboloidal bodies - Dat, Nguyen Tien (Vietnam Journal of Mechanics, 1997)
In this paper, wave forces acting on axisymmetric paraboloidal bodies are considered by using numerical model presented in [1]. The optimum of wave forces is obtained in the case of constant Volume and constant wetted surface of the bodies.